STRATEGI DIGITAL MARKETING DALAM UPAYA MENINGKATKAN PENJUALAN PADA TOKO RAFIF CELL RAJABASA BANDAR LAMPUNG - Robbi Firman Saputra; Vonny Tiara (CV. Lafadz Jaya, 2026)
This study aims to analyze the implementation of digital marketing strategies used by Toko Rafif Cell to increase sales and develop its business. The analysis was conducted using the SWOT method through the IFAS and EFAS Matrices to identify internal and external factors that influence the business. The study used a qualitative descriptive approach with primary and secondary data sources. Data collection techniques were carried out through observation, interviews, and documentation. The results of the study indicate that digital marketing strategies implemented through social media can have a positive impact on increasing sales turnover. Based on the results of the IFAS analysis, Toko Rafif Cell has quite good internal strengths, while the results of the EFAS show the business's ability to capitalize on opportunities and face threats from business competition.